The EIF SME Access to Finance Index - October 2021 update - Wouter Torfs (European Investment Fund (EIF), 2021)
This working paper elaborates on the most recent update of the EIF SME Access to Finance (ESAF) Index, a composite indicator used to monitor the state of SME external financing markets in the 27 EU countries. The current update, using the latest available data, constitutes the eight iteration of this exercise. The paper provides some background information underlying the ESAF results for 2020, which are the latest available data at the time of writing. The results capture the initial impact of COVID-19 crisis and the subsequent policy response.
Keywords: 330